2015
DOI: 10.3389/fnagi.2015.00023
|View full text |Cite
|
Sign up to set email alerts
|

Emotional memory for musical excerpts in young and older adults

Abstract: The emotions evoked by music can enhance recognition of excerpts. It has been suggested that memory is better for high than for low arousing music (Eschrich et al., 2005; Samson et al., 2009), but it remains unclear whether positively (Eschrich et al., 2008) or negatively valenced music (Aubé et al., 2013; Vieillard and Gilet, 2013) may be better recognized. Moreover, we still know very little about the influence of age on emotional memory for music. To address these issues, we tested emotional memory for musi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 115 publications
2
21
1
1
Order By: Relevance
“…Thus, the memory performance for stimuli associated with positive valence was not only higher than for negative ones, but also improved after a 24-h delay, which was not the case for the negative stimuli. The fact that emotional enhancement on musical memory varies as a function of study-test delay intervals confirmed our predictions and is compatible with previously reported results ( Alonso et al, 2015 ). It suggests that post-encoding processes, including consolidation that transforms newly formed memories from a fragile state to a more permanent state, modulated the effects of emotion upon musical memory.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Thus, the memory performance for stimuli associated with positive valence was not only higher than for negative ones, but also improved after a 24-h delay, which was not the case for the negative stimuli. The fact that emotional enhancement on musical memory varies as a function of study-test delay intervals confirmed our predictions and is compatible with previously reported results ( Alonso et al, 2015 ). It suggests that post-encoding processes, including consolidation that transforms newly formed memories from a fragile state to a more permanent state, modulated the effects of emotion upon musical memory.…”
Section: Discussionsupporting
confidence: 93%
“…The musical material consisted of 32 symphonic excerpts with a duration of 5 s (±1-s fade and in fade out) already used in a previous study ( Alonso et al, 2015 ). These excerpts were taken from different symphonies written by composers between 1830 and 1954 and were normalized to a maximal amplitude of 1.2 dB.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations